An Action Plan for Resolving the Grave Water Crisis Facing Dewas Town A Research Study Prepared for the Planning Commission - Planning Commission (Planning Commission, 1994)
The last two decades have witnessed the emergence of a grave water crisis that threatens to envelop the entire country. What is most disturbing is that the crisis has spread even to several sub-humid areas, where it seems to have been a consequence of the nature of the development effort itself. A striking illustration is provided by the experience of the town of Dewas in western Madhya Pradesh, located about 35 km. north-east of Indore (see Map 1). Dewas, since the 1980s, has found itself in the throes of a severe water crisis which only seems to get worse by the year.
Planning Commission Government of India
Planning Commission Government of India